2021
DOI: 10.1177/1945892421992659
|View full text |Cite
|
Sign up to set email alerts
|

Educational Informed Consent Video Equivalent to Standard Verbal Consent for Rhinologic Surgery: A Randomized Controlled Trial

Abstract: Background Informed consent is an integral part of pre-operative counseling. However, information discussed can be variable. Recent studies have explored the use of multimedia in providing informed consent for rhinologic surgery. Objective To measure impact of an educational video (Video) compared to verbal informed consent (Verbal) on knowledge gained, alleviation of concerns, and efficiency. Methods Patients undergoing endoscopic sinus surgery (ESS), septoplasty, or ESS+septoplasty were prospectively enrolle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 42 publications
(88 reference statements)
0
14
0
Order By: Relevance
“…A total of 3842 patients were included in studies. Comprehension was assessed in 38 studies 11 , 15 , 28–63 , satisfaction in 24 28 , 31 , 33–39 , 43–45 , 47 , 49 , 50 , 52 , 54–56 , 58 , 59 , 63–65 , anxiety in 16 studies 29 , 31–33 , 35 , 44 , 46 , 47 , 49 , 50 , 52 , 53 , 56 , 58–60 , 65 , and time taken face to face with the treating clinician in seven studies 34–36 , 52 , 57 , 60 . Thirty-nine studies specified that the trial setting was for elective surgery and only one study was carried out for an emergency procedure 37 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 3842 patients were included in studies. Comprehension was assessed in 38 studies 11 , 15 , 28–63 , satisfaction in 24 28 , 31 , 33–39 , 43–45 , 47 , 49 , 50 , 52 , 54–56 , 58 , 59 , 63–65 , anxiety in 16 studies 29 , 31–33 , 35 , 44 , 46 , 47 , 49 , 50 , 52 , 53 , 56 , 58–60 , 65 , and time taken face to face with the treating clinician in seven studies 34–36 , 52 , 57 , 60 . Thirty-nine studies specified that the trial setting was for elective surgery and only one study was carried out for an emergency procedure 37 .…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-five studies reported results on digital consent with PPP ( Table S2 ). Video-only interventions were reported in 15 of 25 (60 per cent) studies 29 , 36 , 37 , 39 , 41 , 44 , 45 , 50 , 51 , 53 , 57 , 60 , 61 , 63 , 65 , non-interactive PowerPoint presentations with audio-visual content in 3 of 25 (12 per cent) studies 11 , 43 , 46 , and via a website in 2 of 25 (8 per cent) studies 47 , 49 . Five studies (20 per cent) had multicomponent interventions 30–32 , 35 , 54 and all five used video and written pamphlets in the intervention group ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the randomized, controlled study by Penn and co-workers is very interesting in showing that an educational informed consent video can be equivalent to a standard verbal consent. 23 However, such an application clearly would require careful thought about the content and delivery.…”
mentioning
confidence: 99%
“…The results of the randomized, controlled study by Penn and co-workers is very interesting in showing that an educational informed consent video can be equivalent to a standard verbal consent. 23 However, such an application clearly would require careful thought about the content and delivery. If key details are omitted, the video consent method could end up being added to the list of common medical malpractice allegations such as those presented in the study by Coppess et al 24…”
mentioning
confidence: 99%